High-resolution monitoring of the pH under strong La Niña conditions in Gorgona Island, Colombian Pacific, Panama Bight - Murcia, Andrea; Acosta, Alberto; Garcia, Alejandro P.; Corredor-Acosta, Andrea; Hernández‑Ayón, José Martín; Guitiérrez, Simón; Celis, Crispín; Ruiz-Pino, Diana (Frontiers in Marine Science, 2025)
Few studies have investigated the potential drivers of high-resolution (daily and 24-hour scales) on ocean acidification (OA) and the carbonate system in a coastal estuary during an intense La Niña event. Therefore, we conducted the first high-resolution total scale pH (pHT) monitoring every three hours for 56 days (13 September to 7 November 2021) at the Colombian Pacific in El Muelle reef, Gorgona National Natural Park. Two moored autonomous submersible instruments (iSAMI-pH and CTD-Diver) were deployed at a depth of 2 m in an area influenced by extreme precipitation, river discharge, semi-diurnal tides, and southwest winds during La Niña 2020-2023. Total alkalinity was derived from salinity data and used alongside pHT to calculate sea surface seawater partial pressure of CO2 (pCO2w; μatm), dissolved inorganic carbon (DIC; μmol kg-1), and omega aragonite saturation (Ωa). The findings suggest that the observed low pH (7.93) and aragonite saturation state (Ωa = 2.22) values are likely attributed to increased precipitation. This enhanced precipitation resulted in higher river discharge, transporting naturally low-pH water to the island via mixing mechanisms (RiOMar type 2). Daily, decreasing solar radiation may reduce the seawater temperature, simultaneously elevating the pCO2w levels and reducing pHT. In contrast, elevated precipitation may reduce surface seawater salinity through freshwater dilution. Throughout the diurnal cycle, peak pHT values were recorded during late afternoon hours, likely driven by photosynthetic activity, while minimum values coincided with early morning periods of maximal respiratory activity. These results underscore the dynamic nature of this area and emphasize the need for long-term evaluation.